"Dental Floss Test (DFT)": A Novel Pre-Surgical Patient Education Tool for Planning Subcutaneous Spinal Cord Stimulator (SCS) Generator Placement. (16th November 2020) - Petersen, Erika A; Reckling, Tiffany
Abstract: INTRODUCTION: SCS is effective for chronic neuropathic pain, contributing to lower opioid use and improvements in pain and quality of life. However, device-related pain can contribute to device explantation[1].We assessed the impact of a novel patient education tool, the "Dental Floss test" or DFT, on device-related pain. [1]Simopoulos T, Aner M, Sharma S, Ghosh P, Gill JS. Explantation of Percutaneous Spinal Cord Stimulator Devices: A Retrospective Descriptive Analysis of a Single-Center 15-Year Experience. Pain Med. 2019 Jul 1;20(7):1355-1361. doi: 10.1093/pm/pny245. METHODS: A new approach to patient education about optimal surgical location for the SCS implanted pulse generator (IPG) was developed with the aim of reducing chronic device discomfort and to improve overall patient satisfaction with the implanted system. Patients underwent standard preoperative evaluation and pre-surgical counseling per the center's neuromodulation protocol for spinal cord stimulator implants. As part of this, patients were coached about recharging, IPG size and weight, and suggestions on optimal position. They were instructed to practice the location using a template "dental floss box" to ensure comfort. Patients implanted for over 2 months completed a 6-question survey to assess the utility of the education and the DFT in planning the IPG location. VAS scores and SCS utilization were also reviewed. RESULTS: 25 patients completed the survey. The majority had used the DFT to plan IPG position. Those who did not cited several reasons: implanted at another center, forgot to perform the DFT, or chose to follow recommendation of surgeon or device company representative without performing the DFT. Of those who used the DFT, 100% were satisfied with location. 95% found the DFT helpful. Pain VAS score and other measures are summarized. CONCLUSION: The educational impact of the DFT appeared successful based on our initial survey cohort. Within the small sample, these patients denied IPG device-site complaints. Patient education and reinforcement of patient autonomy in the surgical planning process appear to contribute to satisfaction with outcomes.